Orexin-A Excites Airway Vagal Preganglionic Neurons via Activation of Orexin Receptor Type 1 and Type 2 in Rats - Chen, Yonghua; Guo, Yuhong; Yan, Xianxia; Zeng, Ming; Chen, Hong; Qiu, Dongying; Wang, Jijiang (Frontiers in Cellular Neuroscience, 2019)
Airway vagal nerves play a predominant role in the neural control of the airway, and augmented airway vagal activity is known to play important roles in the pathogenesis of some chronic inflammatory airway diseases. Several lines of evidence indicate that dysfunctional central orexinergic system is closely related to the severity of airway diseases, however, whether orexins affect airway vagal activity is unknown. This study investigates whether and how orexin-A regulates the activity of medullary airway vagal preganglionic neurons (AVPNs).The expression of orexin receptor type 1 (OX1R) and type 2 (OX2R) was examined using immunofluorescent staining. The effects of orexin-A on functionally identified inspiratory-activated AVPNs (IA-AVPNs), which is critical in the control of airway smooth muscle, were examined using patch-clamp in medullary slices of neonatal rats. Airway vagal response to injection of orexin-A into the magna cisterna was examined using plethysmography in juvenile rats. The results show that retrogradely labeled AVPNs were immunoreactive to anti-OX1R antibody and anti-OX2R antibody. Orexin-A dose-dependently depolarized IA-AVPNs and increased their firing rate. In synaptically isolated IA-AVPNs, the depolarization induced by orexin-A was blocked partially by OX1R antagonist SB-334867 or OX2R antagonist TCS OX2 29 alone, and completely by co-application of both antagonists. The orexin-A-induced depolarization was also mostly blocked by Na+/Ca2+ exchanger inhibitor KB-R7943. Orexin-A facilitated the glutamatergic, glycinergic and GABAergic inputs to IA-AVPNs, and the facilitation of each type of input was blocked partially by SB-334867 or TCS OX2 29 alone, and completely by co-application of both antagonists. Injection of orexin-A into the magna cisterna of juvenile rats significantly increased the inspiratory and expiratory resistance of the airway and consequently decreased the dynamic compliance of the lungs, all of which were prevented by atropine sulphate or bilateral vagotomy. These results demonstrate that orexin-A excites IA-AVPNs via activation of both OX1R and OX2R, and suggest that increased central synthesis/release of orexins might participate in the pathogenesis of airway diseases via over-activation of AVPNs.